(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Microemulsions are thermodynamically stable transparent or translucent formulations which contain mainly oil, water, surfactantsand co-surfactants. The aim of the present study was to develop and evaluate microemulsion for the topical drug delivery offluconazole (FLZ). The solubility of fluconazole in different oils, surfactants and co-surfactants was selected to identify thecomponents of the microemulsion. The pseudo-ternary phase diagrams were constructed using the water titration method at ambienttemperature. The selected microemulsions were assessed for globule size, zeta potential conductivity, viscosity, spreadability, pH andstability study, Besides this, the microemulsion loaded fluconazole formulations were evaluated for and in vitro permeation studiesand skin irritation studies .In-vitro permeation studies performed through wister rat skin membrane. The optimized microemulsionFLZ MEs-1 and FLZ MEs-6formulations consisting of FLZ 1%, castor oil 10%- 20% respectively, Smix(4:1, 2:1), 50%- 48%respectively and aqueous phase 39%-31% respectively. The in vitro permeation through excised Wister rat skin from the studiedmicroemulsion was best described by the zero-order and first order models. Finally, the optimized FLZ MEs-1 formulations showedhigher activity as compared to that of FLZ MEs-6 respectively. The results suggest the potential use of developed microemulsion asvehicles for topical drug delivery of fluconazole, encouraging further in vitro evaluation.